Answer:
![y(x)=e^(-3x)[C_1cos(2x)+C_2sin(2x)]](https://img.qammunity.org/2023/formulas/mathematics/college/vw2gdy6u5i0eux6ysa0ynw222kjifll3zi.png)
Explanation:
To solve a second-order homogeneous differential equation, we need to substitute each term with the auxiliary equation
where the values of
are the roots:
![y''+6y'+13y=0\\\\m^2+6m+13=0\\\\m^2+6m+13-4=0-4\\\\m^2+6m+9=-4\\\\(m+3)^2=-4\\\\m+3=\pm2i\\\\m=-3\pm2i](https://img.qammunity.org/2023/formulas/mathematics/college/m69wv897buaa0rq7dcb5js4b675w5r9982.png)
Since the values of
are complex conjuage roots, then the general solution is
where
.
Thus, the general solution for our given differential equation is
.